CHARLES DICKENS AS A FOUNDER OF CHRISTMAS GENRE IN LITERATURE - Eshniyozova Jasmina Jo’rabekovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This topic explores the enduring significance of Charles Dickens' literary contributions, focusing on his adeptness at social criticism and comedic characterizations. It highlights Dickens' groundbreaking portrayal of the impoverished with authenticity and empathy, emphasizing his impact during the Victorian era. The paragraph also acknowledges criticisms of Dickens' early works for their emotional theatrics but applauds his evolution as a writer. Furthermore, it discusses Dickens' exploration of societal issues and the plight of female characters, advocating for a greater understanding of discriminatory practices for societal progress. Additionally, the passage discusses Dickens' influence on younger audiences, particularly through works like "A Christmas Carol," which is celebrated for its themes of redemption and the importance of empathy. Overall, the extract underscores Dickens' legacy as a literary genius whose works continue to resonate with audiences worldwide.